PERANCANGAN KEMASAN PRODUK SAGUN BAKAR JONJANG SARIBU - Farhan Wardana Putra (IAM Indonesia, 2023)
This design is motivated by the old packaging on Sagun Bakar Jonjang Saribu which is old-fashioned and less attractive, especially for the younger generation. In the process of designing Sagun Bakar Jonjang Saribu Packaging, the author needs data that will help him in the design process, which is done through observation and interviews. From the data, analysis is carried out using data analysis methods, namely the 5W + 1H analysis theory (what, who, when, why, where, and how). Furthermore, making the concept of creative strategies and programs in producing design problem solving. The design process produces Sagun Bakar Jonjang Saribu packaging design as the main media in the form of packaging that has visual elements and attractive shapes, visual messages that provide information about Sagun Bakar Jonjang Saribu, the results of this design can later be used by Sagun Bakar Jonjang Saribu as a new packaging that is more attractive and modern. Keywords: Promotional Media, Packaging, Sagun Bakar Jonjang Saribu.